Cardiometabolic risk factors and survival after breast cancer in the Women's Health Initiative. Issue 8 (16th January 2018) - Simon, Michael S.; Beebe‐Dimmer, Jennifer L.; Hastert, Theresa A.; Manson, JoAnn E.; Cespedes Feliciano, Elizabeth M.; Neuhouser, Marian L.; Ho, Gloria Y. F.; Freudenheim, Jo L.; Strickler, Howard; Ruterbusch, Julie; Barac, Ana; Chlebowski, Rowan; et al.
Abstract : BACKGROUND: Few studies have examined the relationship between cardiometabolic risk factors linked to metabolic syndrome and mortality among women with breast cancer. METHODS: We used the Women's Health Initiative to evaluate the relationship between cardiometabolic risk factors, including waist circumference (WC), blood pressure, cholesterol level, and presence of type 2 diabetes, and their relation with death from breast cancer, cardiovascular disease (CVD), and other causes among 8641 women with local or regional stage invasive breast cancer. Cox proportional hazards models were used to estimate hazard ratios, and 95% confidence intervals, adjusted for important predictors of survival. RESULTS: After a median of 11.3 years, there were 2181 total deaths, 619 (28.4%) of which were due to breast cancer. Most participants (55.7%) had at least 2 cardiometabolic risk factors, and 4.9% had 3 or 4. Having a larger number of risk factors was associated with higher risk of CVD and other‐cause mortality ( P trend < .001 for both), but not with breast cancer mortality ( P trend = .86). Increased WC was associated with a higher risk of CVD (hazard ratio [HR], 1.28; 95% confidence interval [CI], 1.05‐1.57) and other‐cause mortality (HR, 1.32; 95% CI, 1.16‐1.49) and only with a small and nonsignificant higher risk of breast cancer mortality (HR, 1.19; 95% CI, 0.93‐1.52). The results did not differ in analyses stratified by race, hormone receptor status, or after an analysis of cases diagnosed within 5 years after baseline. CONCLUSIONS: Among women with early stage breast cancer, cardiometabolic risk factors are significantly associated with cardiovascular and other‐cause mortality, but not breast cancer mortality. Cancer 2018;124:1798‐807 . © 2018 American Cancer Society Abstract : Cardiometabolic risk factors are positively associated with higher mortality from cardiovascular disease and other causes, but not with higher risk of death from breast cancer in postmenopausal women with breast cancer. Identifying and managing cardiometabolic risk factors should be standard of care for all postmenopausal women diagnosed with breast cancer.